Toward an Integrative ESD-Based Curriculum Management Model for Junior High Schools: A Systematic Literature Review - Martza Merry Swastikasari; Sucihatiningsih Dian Wisika Prajanti; Joko Widodo; Mintarsih Arbarini (Universitas Negeri Semarang, 2026)
Abstract The junior high school level has a strategic position in the implementation of ESD. Students at this level of education are in the early phase of adolescence and begin to develop. The existing literature demonstrates that ESD implementation in junior high schools is influenced by multiple interconnected factors, which are often examined in isolation. This study aims to identify patterns of ESD integration, map the dimensions that facilitate its implementation, and develop a conceptual model of ESD-based curriculum management for junior high schools. This study uses a Systematic Literature Review following the PRISMA 2020 framework. The literature was obtained from Scopus and Google Scholar, then selected based on inclusion-exclusion criteria, yielding 31 articles that were analyzed thematically. The results of the study show five patterns of ESD integration, four facilitating dimensions, and a final synthesis that forms an integrative model connecting curriculum design, implementation, evaluation, continuous improvement, learning outcomes, and enabling factors. This study found that ESD integration at the junior high school level does not follow a linear process (content is included–teacher teaches–students understand). Future studies should refine the systematic review protocol by implementing more specific and comprehensive search strategies, while maintaining transparent and rigorous eligibility criteria.